The experience of the movement as a possible reading of the dynamic landscape (ARQUISUR Revista, 2019)
The present article of reflection is the result of the research of an ongoing doctoral thesis, where the notions of "landscape" and "road" are linked, which advance towards the construction of the "landscape-in-movement perception". The empirical component consists in journey through a local route and the description of the itinerary, in order to demonstrate that displacements along interurban roadways can constitute a valuable resource of perception and appropriation of the landscape, in line with its dynamic conception. As a conclusion, there is a recognition of a space rich in landscape scenarios and sensorial potentials. This is a continuous, sequential, changing and fleeting natural path. A game between what is seen and what is not: the sighting and the concealment, the sudden disappearance of these water bodies and the expectation of their visibility. On the other hand, the completion of the itinerary leaves many expectations in relation to the use of this landscape trying to overcome the instance of a scenario to be contemplated, to conceive the landscape as a key element which forms a material part of the road project.
Keywords: space; perception; representation; journey; road